Springer Tracts in Advanced Robotics
DOI: 10.1007/3-540-36460-9_17
|View full text |Cite
|
Sign up to set email alerts
|

Collaboration, Dialogue, Human-Robot Interaction

Abstract: Teleoperation can be improved if humans and robots work as partners, exchanging information and assisting one another to achieve common goals. In this paper, we discuss the importance of collaboration and dialogue in human-robot systems. We then present collaborative control, a system model in which human and robot collaborate, and describe its use in vehicle teleoperation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
156
0
4

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(163 citation statements)
references
References 11 publications
3
156
0
4
Order By: Relevance
“…In addition, the necessary complexity in autonomous solutions (e.g. [5,7]) warrants the need of trust. Finally, these setups are relevant to a wide variety of different robot platforms and application contexts.…”
Section: Interaction Contextmentioning
confidence: 99%
“…In addition, the necessary complexity in autonomous solutions (e.g. [5,7]) warrants the need of trust. Finally, these setups are relevant to a wide variety of different robot platforms and application contexts.…”
Section: Interaction Contextmentioning
confidence: 99%
“…Fong, Thorpe, and Baur found that by having humans collaborate with multiple independently-controlled robots, both were able to accomplish more than when the humans had to manually control every aspect of the robots [11]. Hinds, Roberts, and Jones studied the effects of different robot appearances and different robot status roles on the task-solving capabilities of different human-robot collaborative pairs [13].…”
Section: A Related Workmentioning
confidence: 99%
“…Although the robotics and machine learning communities are working to develop human-level competence, robots still have difficulty with many skills that come naturally to humans. For example, robots have difficulty with perceptual tasks in cluttered or complex terrain (Nguyen-Huu, Titus, Tilbury, & Ulsoy, 2009), and robots have difficulty resolving ambiguity in their high-level perceptual tasks (Fong, Thorpe, & Baur, 2003).…”
Section: Human Assistance Provided To Robotsmentioning
confidence: 99%